FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN DEFENSIVE DRIVING PADA PENGEMUDI BUS RAPID TRANSIT (BRT) TRANS SEMARANG KORIDOR II, III, DAN VI - Yuwan Martus Tegar Charisma; Ekawati Ekawati; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Defensive driving is a driving skill to defend himself from possible accidents caused by bad driver behavior. Drivers become one of the factor that cause traffic accidents, such as lack of anticipation, negligence, and driving under the influence of alcohol. An understanding of good defensive driving practices of Bus Rapid Transit (BRT) Trans Semarang’s driver aims to make the driver more defensive, alert, and able to anticipate the situation so there is no traffic accident. The aim of this study was to analyze factors related the defensive driving of Bus Rapid Transit (BRT) Trans Semarang’s driver corridor II, III, and VI. This type of research is analytic survey with cross sectional study approach. Population of this study was all of Bus Rapid Transit (BRT) Trans Semarang’s driver corridor II, III, and VI were 83 respondents and the number of sample in this study were 43 respondents. Sampling techniques of this study was proportional random sampling. Data were collected by using questionnaire and observation. Data were analyzed using chi square test. The result shows that variables related to the defensive driving of Bus Rapid Transit (BRT) Trans Semarang’s driver corridor II, III, and VI were knowledge (p=0,024), attitude (p=0,001), perception (p=0,005), bus condition (0,004), supervisor role (0,001) and variables unrelated to the defensive driving were defensive driving training (p=1,00) and friends support (p=0,767). This research suggests that defensive driving training must be provided to drivers, seat belt safety campaigns for all passengers, and create a discussion about defensive driving every week.